2014
DOI: 10.3892/or.2014.3268
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K/mTOR dual inhibitor NVP-BEZ235 reduces the growth of ovarian clear cell carcinoma

Abstract: Abstract.Patients with clear cell carcinoma of the ovary (OCCC) have poor survival due to resistance to standard chemotherapy. OCCC has frequent activating mutations of the PIK3CA gene. The present study was conducted to clarify the efficacy of the inhibition of the PI3K-AKT-mTOR pathway in OCCC. We used 8 OCCC cell lines and 5 ovarian serous adenocarcinoma (OSAC) cell lines. The mutation status of the PIK3CA and KRAS genes was examined by direct sequencing. The IC 50 values of NVP-BEZ235 (BEZ235) and temsirol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
3
21
0
1
Order By: Relevance
“…These results are in accordance with the results of Shoji et al and Oishi et al, who used commercial EC cell lines and ovarian clear cell carcinoma cell lines, respectively [17,30]. In hepatocellular carcinoma, however, Kirstein et al indicated that NVP-BKM120 has a higher antitumor activity compared to RAD001 (mTORC1 inhibitor) and NVP-BEZ235 [31].…”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with the results of Shoji et al and Oishi et al, who used commercial EC cell lines and ovarian clear cell carcinoma cell lines, respectively [17,30]. In hepatocellular carcinoma, however, Kirstein et al indicated that NVP-BKM120 has a higher antitumor activity compared to RAD001 (mTORC1 inhibitor) and NVP-BEZ235 [31].…”
Section: Discussionsupporting
confidence: 93%
“…This is in contrast to HGSCs, which are characterized by frequent mutations of TP53 – up to 96% as reported in The Cancer Genome Atlas (TCGA) [26]. A trial of NVP-BEZ235, a dual PI3K/mTOR inhibitor, showed promise in OCCC cell lines [27], and may warrant further investigation. There is an ongoing phase II GOG trial for dasatinib (GOG 283) in recurrent/persistent OCCC and endometrial CCC characterized for retention or loss of BAF250a expression, a protein encoded by ARID1A .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous in vitro and in vivo studies have investigated the activity of direct PI3K and mTOR inhibition and have found significant activity in clear cell, mucinous and high grade serous ovarian cancer models [61][62][63][64]. While the frequency of PIK3A gene mutation was highest in ovarian clear cell carcinomas, this alteration did not appear to associate with response to PI3K or mTOR inhibitors [61,[65][66][67]. A recent study utilized a model of endometrioid ovarian carcinoma finding that the greatest effects of mTOR or AKT inhibition were derived in the setting of concurrent conventional cyctotoxic chemotherapy [12].…”
Section: Ovarian Cancermentioning
confidence: 96%